Effects of exercise training on coronary collateralization and control of collateral resistance - Heaps, Cristine L. (American Physiological Society, 2011)
Coronary collateral vessels serve as a natural protective mechanism to provide coronary flow to ischemic myocardium secondary to critical coronary artery stenosis. The innate collateral circulation of the normal human heart is typically minimal and considerable variability occurs in extent of collateralization in coronary artery disease patients. A well-developed collateral circulation has been documented to exert protective effects upon myocardial perfusion, contractile function, infarct size, and electrocardiographic abnormalities. Thus therapeutic augmentation of collateral vessel development and/or functional adaptations in collateral and collateral-dependent arteries to reduce resistance into the ischemic myocardium represent a desirable goal in the management of coronary artery disease. Tremendous evidence has provided documentation for the therapeutic benefits of exercise training programs in patients with coronary artery disease (and collateralization); mechanisms that underlie these benefits are numerous and multifaceted, and currently under investigation in multiple laboratories worldwide. The role of enhanced collateralization as a major beneficial contributor has not been fully resolved. This topical review highlights literature that examines the effects of exercise training on collateralization in the diseased heart, as well as effects of exercise training on vascular endothelial and smooth muscle control of regional coronary tone in the collateralized heart. Future directions for research in this area involve further delineation of cellular/molecular mechanisms involved in effects of exercise training on collateralized myocardium, as well as development of novel therapies based on emerging concepts regarding exercise training and coronary artery disease.